GIS-based irrigation potential assessment on Shaya River sub-basin in Bale Zone, Oromia region, Ethiopia - Nasir Gebi Tukura; Tolera Abdisa Feyissa (Brawijaya University, 2020)
The principal objective of this study was to evaluate the land resources potential of the fertile Shaya River sub-basin for irrigation and amply providing a Geo-referenced map of these valuable resources using Geographical Information System (GIS) techniques. Suitability factors considered to identify the potentially irrigable land were the slope, texture, depth, drainage characteristics, land use/cover and distance to a water source. The suitability analysis of the parameters indicates that slope 66.38%, soil 98.20% and land use/cover 92.93% of the study areas classified as potentially suitable for irrigation development in the study area. By weighing analysis of all parameters, 22.05% of the study area was found to be highly suitable, 25.27% moderately suitable and 16.20% marginally suitable whereas about 33.57% restricted for irrigation developments. By comparing the required water and available monthly flow of the river, the river possesses the capacity for the application of the command area.